PRESERVATION OF ORNAMENTATION AND SPATIAL SANCTITY AS DETERMINANTS OF DESTINATION VISUAL IDENTITY HERITAGE TEMPLE IN LOMBOK - Ahmad Ghazy Dananjaya (INTERNATIONAL JOURNAL ON HINDU CULTURE, 2026)
This study aims to quantitatively analyze the influence of architectural ornamentation and spatial sanctity on the visual identity of cultural tourism destinations in West Nusa Tenggara (NTB), Indonesia. The research locus encompasses four pivotal heritage sites: Pura Lingsar, Pura Batu Bolong, Pura Suranadi, and Pura Gunung Pengsong. This research employs a quantitative approach with an explanatory survey design. Primary data were collected from 200 respondents (tourists) using a structured questionnaire with a 7-point Likert scale. The sampling technique used was purposive sampling. Data analysis was performed using Multiple Linear Regression and Classical Assumption Tests via SPSS to test the hypotheses. The statistical results demonstrate that both architectural ornamentation and spatial sanctity have a positive and significant effect on the destination's visual identity, both partially and simultaneously (R2 > 0.6). The study empirically proves that strict adherence to sacred zoning rules (Tri Mandala) significantly enhances, rather than diminishes, the destination's visual appeal and branding. This study provides empirical evidence linking theological spatial concepts directly to destination marketing metrics in non-Balinese Hindu heritage sites, filling a gap in the quantitative literature on spiritual tourism.